Spin configuration in isolated FeCoCu nanowires modulated in diameter. (2nd October 2015) - Iglesias-Freire, Óscar; Bran, Cristina; Berganza, Eider; Mínguez-Bacho, Ignacio; Magén, César; Vázquez, Manuel; Asenjo, Agustina
Abstract Cylindrical Fe28Co67Cu5 nanowires modulated in diameter between 22 and 35 nm are synthesized by electroplating into the nanopores of alumina membranes. High-sensitivity MFM imaging (with a detection noise of 1 μN m−1) reveals the presence of single-domain structures in remanence with strong contrast at the ends of the nanowires, as well as at the transition regions where the diameter is modulated. Micromagnetic simulations suggest that curling of the magnetization takes place at these transition sites, extending over 10–20 nm and giving rise to stray fields measurable with our MFM. An additional weaker contrast is imaged, which is interpreted to arise from inhomogeneities in the nanowire diameter.